Coping Assessment Tools in the Family Caregivers of Patients with Breast Cancer: A Systematic Review - Jahani Sayad Noveiri M (Dove Medical Press, 2020)
Marzieh Jahani Sayad Noveiri,1 Farshid Shamsaei,2 Masoud Khodaveisi,3 Zohreh Vanaki,4 Lily Tapak5 1Student Research Committee, Hamadan University of Medical Sciences, Hamadan, Iran; 2Mother and Child Care Research Center, Hamadan University of Medical Sciences, Hamadan, Iran; 3Chronic Diseases (Home Care) Research Center, Department of Community Health Nursing, Hamadan University of Medical Sciences, Hamadan, Iran; 4Department of Nursing, Faculty of Medical Sciences, Tarbiat Modares University, Tehran, Iran; 5Department of Biostatistics, School of Public Health, Modeling of Noncommunicable Diseases Research Center, Hamadan University of Medical Sciences, Hamadan, IranCorrespondence: Farshid ShamsaeiSchool of Nursing & Midwifery, Hamadan University of Medical Sciences, Shahid Fahmideh Bulv., Hamadan 65178, IranTel +98-81-38381941Fax +98-81-38381942Email shamsaei68@yahoo.comBackground: Breast cancer is a problem that affects not only the individual’s health and quality of life, but also the functionality of the family system. Caregivers experience stress when their patients cannot cope with the symptoms of their disease. The stress experienced by caregivers gives rise to psychological and physical symptoms in them. This study seeks to present a complete set of tools for assessing coping in the spouses or caregivers of women with breast cancer and evaluate the various instruments developed within these lines of inquiry.Methods: A search was carried out in PubMed, Scopus, Web of Science, CINAHL, PsycINFO, Medline, ProQuest, Scopus and Google Scholar and also in the reference lists of the key articles retrieved for any coping assessment instrument targeting family caregivers’ needs that had acceptable psychometric properties and was published until September 2019. The instruments used to assess coping in the spouses and caregivers of women with breast cancer were thus identified and their properties were described.Results: Overall, 88 adaptation assessment tools related to family caregivers of patients with breast cancer were identified in 28 related articles. The tools examine different dimensions of adaptation such as satisfaction, stress, burden and needs of spouses and caregivers of patients with breast cancer.Conclusion: Assessing family caregivers’ coping is essential for providing them with the appropriate sources of support. Although several instruments have been used to assess coping in the spouses and caregivers of women with breast cancer, the properties of these instruments have to be examined before they can be more widely implemented.Keywords: coping, assessment tools, caregivers, breast cancer, family